Development of Customer Loyalty Model on Online Transportation Service: A Case Study in Indonesia - Budhi Prihartono; Karina Rizky Ismantia; Fidruzal Fahlevi (Jurnal Teknik Industri, 2023)
The impact of technology on public transport has led to a new online transportation service. Its emergence makes the competition increasingly competitive. Therefore, customer loyalty becomes an important aspect of winning the competition. This research analyzed the effect of customer service, service delivery, onboard experience, public image, service value, and customer satisfaction on customer loyalty to online transportation. 517 respondents were obtained and divided into two groups: captive rider and choice rider. Data processing is carried out using a multigroup SEM technique. The results showed that there was a significant moderation effect of the different characteristics of users. In the captive rider group, onboard experience and service value did not affect customer satisfaction, and service value did not affect customer loyalty. Customer satisfaction influenced customer loyalty, and the effect was more robust than the choice rider group. In the choice rider group, the public image did not affect customer satisfaction, but service value influenced customer loyalty. Factors proven to influence customer loyalty significantly can be developed by companies to improve their competitive advantage in an increasingly competitive market of online transportation services.